MONETARY TRANSMISSION MECHANISM UNDER DUAL FINANCIAL SYSTEM IN INDONESIA: CREDIT-FINANCING CHANNEL - Fikri, Reza Jamilah (Journal of Islamic Monetary Economics and Finance, 2018)
The presence of Islamic and conventional banking in the dual financial system of Indonesia equally hold the role as financial intermediator which theoretically banks collect fund from the debitors to be distributed to creditors. However, along with the changing of time there has been a development in the financial industry, when financial deregulation occurs, where the role of providing credit is not only owned by the banks but also other financial institutions. As the result, banks are no longer considered as the center of financial intermediation but could be replaced by other financial instruments. This study aims to reconsider the role of banking as financial intermediation in the monetary transmission mechanism using three methodoligal approaches which are Vector Autoregression and Vector Error Correction Model (VAR-VECM), Error Correction Model (ECM), and Autoregressive Distributed Lag (ARDL). The long-term results of ECM and VECM estimations both show that credit and finacing channel are still relevant to be employed in the monetary transmission mechanism after the development of financial sector and the change of monetary policy, yet only have an impact to economy and do not give effect to inflation. While the result of ARDL estimation indicates that none of the variables affect the monetary policy objectives which means that credit and financing channel are considered to be getting weaker in the monetary transmission mechanism.